(untitled) (Malaysian Management Journal, 2022)
A disaster cause disruption to the normal patterns of life, as it is usually severe, sudden, unexpected, widespread, and has direct effects on the smooth running of an organization. This article has assessed the role of the facilities manager in disaster management in Lagos, with a particular interest in the pre-disaster measures provided. A quantitative research design using a well-structured questionnaire survey was adopted. Out of the 150 questionnaires distributed, a total of 134 questionnaires were returned duly completed, a response rate of 89.3 percent. The data were analyzed using the computer software SPSS (7th ed.). The result of the analysis revealed that the most common and reoccurring disasters experienced by companies in the study area were, as listed in their order of predominance, as follows: flooding, power outage, civil unrest, fire, and pest disasters. The study found that most firms rarely use the disaster threat information as part of their preparedness plan, nor has developed any disaster response techniques or recovery measures. The study has identified the major roles of a facilities manager in disaster management. These roles ranged from disaster record-keeping for subsequent planning, routine survey of areas prone to disaster, disaster tracking and warning, and public enlightenment on disaster occurrence. The study has recommended that facilities managers ensure that there is good public awareness, functional facilities, good organization and planning, and excellent functional readiness facilities, such as having emergency operations centers.